Features of the formation of biophysical concepts of students in the process of biological education - Жумагулова, Калампыр; Тұрсыматова, Оразкүл; Битибаева, Жазира; Ибадуллаева, Салтанат; Үргенішбеков, Айтмағанбет (Pedagogy and Psychology, 2022)
The article discusses the features of the formation of biophysical concepts in students. The study data were collected using a structured interview form developed by the researchers. As a result of the study, the need for frequent use of concepts that ensure the formation and development of biophysical concepts in students is shown. Biology teachers participating in the research work considered the positive aspects of using conceptual maps that ensure the formation and development of students' biophysical ideas. Concept maps include: concepts about objects that make up the content of natural science education (general concepts, division into concepts, classification, division into smaller types), providing an effective study of the subject, improving the system of thinking, establishing links between concepts, make the lesson interesting and facilitate the assimilation of basic concepts, as well as the logical and structural analysis of individual subjects; structure and properties of objects); basic laws and patterns that characterize objects; processes occurring in the presence of natural scientific objects and their interaction; content networks, such as methods of scientific knowledge of natural objects and processes.